Smart Home Security Using Facial Authentication - Rakshitha, M.V.; Chitra, K. (INTI International University, 2024)
Smart home security enhances security by allowing only authenticated individuals to enter the home. The technology uses advanced algorithms to recognize faces, making them safer and easier to access. The main objective is to improve privacy and security by using facial recognition based on the LBPH technique. The proposed application allows users to keep track of the happenings at their homes using mobile phones, Tablets, or PCs. The system records a flow of people at the door and identifies their faces against the database of the allowed people. If the face is recognized it allows the homeowner access but if the face is not recognized it will sound a warning that there is intrusion. The new face is captured and compared to the existing one and the homeowner then decides where to add the new face for storage.